Early-Onset Parkinson Disease Screening in Patients From Nigeria - Milanowski, Lukasz M.; Oshinaike, Olajumoke; Broadway, Benjamin J.; Lindemann, Jennifer A.; Soto-Beasley, Alexandra I.; Walton, Ronald L.; Hanna Al-Shaikh, Rana; Strongosky, Audrey J.; Fiesel, Fabienne C.; Ross, Owen A.; Springer, Wolfdieter; Ogun, Shamsideen Abayomi; et al. (Frontiers in Neurology, 2021)
Introduction: Nigeria is one of the most populated countries in the world; however, there is a scarcity of studies in patients with age-related neurodegenerative diseases, such as Parkinson disease (PD). The aim of this study was to screen patients with PD including a small cohort of early-onset PD (EOPD) cases from Nigeria for PRKN, PINK1, DJ1, SNCA multiplication, and LRRK2 p.G2019S. Methods: We assembled a cohort of 109 Nigerian patients with PD from the four main Nigerian tribes: Yoruba, Igbo, Edo, and Hausa. Fifteen cases [14 from the Yoruba tribe (93.3%)] had EOPD (defined as age-at-onset <50 years). All patients with EOPD were sequenced for the coding regions of PRKN, PINK1, and DJ1. Exon dosage analysis was performed with a multiplex ligation-dependent probe amplification assay, which also included a SNCA probe and LRRK2 p.G2019S. We screened for LRRK2 p.G2019S in the entire PD cohort using a genotyping assay. The PINK1 p.R501Q functional analysis was conducted. Results: In 15 patients with EOPD, 22 variants were observed [PRKN, 9 (40.9%); PINK1, 10 (45.5%); and DJ1, 3 (13.6%)]. Three (13.6%) rare, nonsynonymous variants were identified, but no homozygous or compound heterozygous carriers were found. No exonic rearrangements were present in the three genes, and no carriers of SNCA genomic multiplications or LRRK2 p.G2019S were identified. The PINK1 p.R501Q functional analysis revealed pathogenic loss of function. Conclusion: More studies on age-related neurodegenerative diseases are needed in sub-Saharan African countries, including Nigeria. Population-specific variation may provide insight into the genes involved in PD in the local population but may also contribute to larger studiesperformed in White and Asian populations.